Importância, diagnose e métodos de inoculação de Xanthomonas albilineans, agente causal da escaldadura-das-folhas em cana-de-açúcar - Moraes, Pedro Oliveira (Universidade Federal de São Carlos, 2024)
Sugarcane is a crop of great economic importance in Brazil; however, the bacterium Xanthomonas albilineans, the causal agent of leaf scald, can impair its productivity. Reported in more than 60 countries, the disease can result in losses of up to 100% in highly susceptible cultivars. The migration of sugarcane cultivation to regions with less agricultural viability and the growth of mechanized harvesting in Brazil have contributed significantly to this pathology being considered one of the most critical in the country's agricultural sector. The symptoms of the disease can present themselves in three different ways: in the latent form, there are no visible external symptoms, only changes in the vascular coloration in the region of the nodes; in chronic cases, white streaks occur on the leaf blade; and, in the acute form, the leaves have a scalded appearance and there are excessive lateral shoots on the stems. The most effective control is the use of resistant varieties and, for this, it is important to evaluate the reaction of the varieties through artificial inoculation of the pathogen and to understand the efficiency of diagnostic methods. In this study, the objective was to explore the importance of leaf scald and to address the methods of inoculation and diagnosis of X. albilineans most commonly used in research on the disease. The most common methods of inoculation are decapitation and inoculation by cutting the leaf blades. As for diagnostic methods, serological and isolation in culture medium are less reliable compared to molecular techniques such as PCR and qPCR. Specifically, qPCR has been shown to be highly effective, offering superior sensitivity, specificity, and efficiency, even at low concentrations of the pathogen. Understanding the importance of the disease, the reaction of sugarcane varieties and the use of efficient diagnostic methods are essential for the control of leaf scald; This information contributes to the protection of the crop and the guarantee of its economic productivity.
Importance, diagnosis and inoculation methods of Xanthomonas albilineans, causal agent of leaf scald in sugarcane
Keywords: Variedades resistentes; Fitossanidade; Bactéria; Saccharum spp; Resistant varieties; Plant health; Bacterium; CIENCIAS AGRARIAS::AGRONOMIA